Results of Molecular Monitoring in Posttransplant Period by Means of Series Investigation of WT1 Gene Expression in Patients with Acute Myeloid Leukemia - YaV Gudozhnikova; NN Mamaev; IM Barkhatov; VA Katerina; TL Gindina; AI Shakirova; SN Bondarenko; OA Slesarchuk; EI Darskaya; OV Paina; LS Zubarovskaya; BV Afanas’ev (Клиническая онкогематология)
Aim. To demonstrate diagnostic and prognostic significance of series measurement of WT1 expression in patients with acute myeloid leukemia (AML) after allogenic hematopoietic stem cell transplantation (allo-HSCT).